Usability testing of the Libro System - Luna edition - Melorin, Pamela P.; Cabbab, Johann Frederick A.; Angeles, Chito N.; Esposo, Sharon Ma. S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
The study is primarily an evaluation of the design of the Libro System-Luna edition by means of a usability test. Usability test is the technique used to evaluate the system by testing it to the actual and potential users. Particularly, it aimed to know how well the Libro System - Luna edition performs in terms of task time, success rate, error rate, memorability rate and satisfaction rate. Also, it intended to gather feedback from the actual and potential users regarding the usability of Libro System - Luna edition after experiencing the usability test.
Five representative users participated in the usability test. This was based on the concept of Nielsen (2000), which states that only five representative users are needed in order to facilitate a usability testing since 85 of the usability problems will be determined after the first study with five users. The main instrument was a series of task scenarios based from the Libro System - Luna edition Manual that the representative users have accomplished. Also, the representative users were asked to answer a pre-test and post test to support the information gathered from the actual test. The results of this study showed that: (1) the longest and shortest average task time consumed in each task per module in the usability test was seemingly accurate and reasonable; (2) there was a significant value of success rates resulting from the usability test, considerably high percentage of success rates manifested in the tasks given; (3) there has been a minimal error obtained in the usability test, thus a significant value of zero error rates resulted from the said test; (4) the level of memorability of proficiency rating of the users obtained from the usability test was proficient, meaning the rating was in the middle level; (5) the perceived satisfaction rate of the users was just satisfied, also in the middle level. The dominant feedback of the users on Libro System - Luna edition was the existence of unnecessary functions that adds up to the confusion and the lack of instructions or help guides on the use of the system.
The researcher recommended that findings of the study be bestowed to the developer of the system so that he could revise and upgrade the system based on the feedback and comments. Particularly, the developer must focus on the revisions of the manual and help guides and the elimination of unnecessary functions such as: add icon in Files and Data Entry Module; add, minus and hours per day icon in Attendance Monitoring Module; statistical Loan Counter since its function is similar to the Loan Transaction History. It is further recommended that the developer of Libro system follow the ten usability heuristics proposed by Nielsen (2005).
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Integrated library systems (Computer systems) -- Philippines -- Use studies; Information services -- Philippines -- Use studies